(untitled) (Medico Legal Update, 2020)
Background :umbilical cord is a fetomaternal tubular organ; it has been described as “dairy of intrauterine life”; this remarkable organ responsible for living of the bay for about 266 days, Where the source of food and oxygen from the mother to the fetus as well as the disposal of waste. Patients and methods :209 umbilical cord and their placentae were studied thoroughly and the mothers ages were 15 -< 45 years old .The length and diameter of the umbilical cord, Wharton’s jelly ,placental weight and umbilical cord insertion were measured .The babies weights were measured and their gender were assigned. Results: current study showed the umbilical cord parameters (length and diameter) have no correlation to mothers’ age groups only in the length and diameter means there were Simple drop in group 1(15_19 year old) and the diameter group 7 (>45 year old ).The umbilical cord knots percentage was normal in comparison to other studies. The study of Wharton’s jelly were correlated with baby’s weight was significant, whenever baby weight increases the Wharton’s jelly increase. And when the Wharton’s jelly Correlate with placenta weight in gm. There was significant correlation.